Working the System : Motion Picture, Filmmakers, and Subjectivities in Mao-Era China, 1949-1966 - He, Qiliang (Book collections on Project MUSE., 2023)
In Working the System: Motion Picture, Filmmakers, and Subjectivities in Mao-Era China, 1949-1966, Qiliang He inquired into the making of the new citizenry in Mao-era China (1949-1976) by studying five preeminent Shanghai-based filmmakers. These case studies shed light on how individuals' subjectivities took shape in the cinematic arena under a new sociopolitical system after 1949. He suggests that a filmmaker's subjectivity was not fixed or stable but constan.